Crown : an ode to the fresh cut - Barnes, Derrick; James, Gordon C. (Walker Books and Subsidiaries, 2021)
The barber shop is where magic happens! Boys go in as lumps of clay and, with princely robes draped around their shoulders, a dab of cool shaving cream on their foreheads and a slow, steady cut, they become royalty, aware of every great thing that could happen to them when they look good. Their grades improve, they get noticed, they feel good about themselves. This rhythmic, read-aloud title is an unbridled celebration of the self-esteem, confidence and swagger boys feel when they leave the barber's chair.
Keywords: hiustenleikkaus; itseluottamus; minäkuva; pojat (ikäryhmät); afroamerikkalaiset; parturi-kampaamot